Eksplorasi Self-Assessment Guru dalam Penguatan Nilai Integritas: Implikasinya Terhadap Kejujuran Akademik dan Resiliensi Psikososial Siswa - Husairi Husairi; Welly Kuswanto (Global Education Journal, 2026)
This study explores teachers' self-assessment practices in enhancing integrity values and their impact on students' academic honesty and psychosocial resilience at TK Restu 1, Malang City. Academic honesty has become a critical issue to examine, given the frequent trend of dishonesty emerging from an early age. This research employed a descriptive qualitative approach. Data were obtained through semi-structured interviews with 10 teachers, classroom observations, and questionnaires distributed to 20 kindergarten students. The collected data were validated through reduction, display, and conclusion-drawing stages. The results indicate that teachers' self-assessment practices significantly impact the effectiveness of character education, with an average score of 4.5. Empirical inspection shows that 90% of students are encouraged to practice honesty, while 88% understand the importance of integrity in learning. These outcomes result from teachers' self-reflection, which fosters positive behavioural frameworks that strengthen students' academic honesty and psychosocial resilience in responding to moral issues. Consequently, this study suggests that educators' self-evaluation is a key instrument in internalizing character within early childhood education. As a practical recommendation, educational institutions should develop teacher self-reflection training programs to further enhance the quality of character education.